PERANAN MEDIA PEMBELAJARAN INTERAKTIF PADA MATERI GENETIKA DNA, GEN, DAN KROMOSOM DALAM PENINGKATAN MINAT BELAJAR BIOLOGI JENJANG SMA/SMK/MA - Lukmanudin, Ali; Aji, Bayu Sindu; Nurkhalia, Nurkhalia; Yusrin, Yusrin (Journal of Lesson Study in Teacher Education, 2023)
The learning process in class both at the elementary, middle and high school levels basically is a process which involves all five senses and also thinking skills. This process will need a relevant learning theory approach with the cognitive development of students and requires learning media that must be in accordance with the level of cognitive development and learning experience of students. The use of learning media in the whole learning process will provide the results of a longer learning experience stored in memory (long term memory). In addition, the use of appropriate learning media in the learning process will result in better cognitive achievement, especially in understanding a concept which in the process of achievement is carried out by the students themselves or guided by the teacher as a learning facilitator. The learning process by utilizing the use of learning media can also involve students directly in using the learning media so that the learning process can achieve the expected goals. As For, the results of the process of using learning media in biology teaching materials in class XII MIPA Muhammadiyah 1 Purwokerto about genetic material genes, DNA, and chromosomes indicate an increased understanding of the concept of a better understanding of this molecular material and can foster student interest in learning.